Solitary dolphins in Spain and recommendations for their management - Laetitia Nunny; Mónica González; Alfredo López; Pablo Covelo; Jose Antonio Martínez-Cedeira; Xabier Pin; Uxía Vázquez; María Macías González; Paula San Martín Lorén; Mark P. Simmonds (Animal Behaviour, 2026)

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Out of habitat marine mammals – Identification, causes, and management recommendations - Laetitia Nunny; Mike Bossley; Rebecca M. Boys; Philippa Brakes; Tilen Genov; E.C.M. Parsons; Katharina J. Peters; Naomi A. Rose; Claire A. Simeone; Karen A. Stockin; Courtney S. Vail; Krista van der Linde; et al. (Marine Policy, 2025)

Vulnerability of Grey Seal Pups (Halichoerus grypus) to Storm Disturbances in the Context of Climate Change: A British Isles Case Study - Keely Saville; Laetitia Nunny; Daniel Jarvis; Sue Sayer; Laszlo Talas; Mark P. Simmonds (Oceans, 2025)
Marine mammals may be particularly vulnerable to climate change. While some climate-change-induced impacts on these species have been recognised, the potential consequences of storminess have been less well-defined, and understanding of its significance largely relies on anecdotal evidence. To quantify the relationship between storminess and its possible impacts on grey seal pups (Halichoerus grypus), data from marine wildlife rescue databases and hospitalisation records (2015–2024) within the British Isles were examined (n = 20,686). Daily mean windspeed was used as a proxy for storminess. Significant relationships were found between storminess and pups presenting with malnourishment, head trauma, flipper injury, other wounds, and infections. This study provides the first empirical evidence of the explicit impacts of storminess on seal pup health, with all the presenting conditions increasing and higher rates of call-outs and pup admissions to rescue centres following stormy weather also recorded. Given the predicted increase in storm severity, these findings will aid rescue and rehabilitation planning by helping to predict when rescuers can anticipate increased admissions and the potential injuries that pups may experience following storms. The potential significance to the long-term conservation of the species is also highlighted.

An investigation into the effects of climate change on baleen whale distribution in the British Isles - Maria Snell; Andrew Baillie; Simon Berrow; Robert Deaville; Rod Penrose; Matthew Perkins; Ruth Williams; Mark P Simmonds (Marine Pollution Bulletin, 2023)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Out of Sight, Out of Mind: How Conservation Is Failing European Porpoises - Ida Carlén; Laetitia Nunny; Mark P. Simmonds (Frontiers in Marine Science, 2021)
The conservation of harbor porpoises ( Phocoena phocoena ) appears to be failing in Europe. There are particular concerns about this species in the Baltic Proper, Black, and Mediterranean Seas, as well as in the Northeast Atlantic, including the Iberian population, off the Spanish and Portuguese coasts. The Baltic Proper porpoise is “critically endangered,” with a population only in the low hundreds, and the Scientific Committee of the International Whaling Commission has repeatedly called for action to ensure its survival. In 2020, the Committee issued a series of recommendations relating to it and the Iberian population. Similarly, the Black Sea harbor porpoise, Phocoena phocoena ssp. relicta , is classified by the IUCN as endangered. Another population which may be genetically distinct is the West Greenland harbor porpoise, which is hunted without quotas or close seasons. European cetaceans and their habitats are covered by a number of international and regional conventions and agreements and, under European Union law, are “highly protected.” In practice, however, these legal protections have failed to generate effective conservation. For example, Special Areas of Conservation (SACs) are required for them and, although sites have been designated in some marine areas/countries, in the absence of appropriate management plans, SACs cannot be expected to help improve the harbor porpoise's conservation status. Compared to many other species, porpoises are relatively long-lived with low reproductive capacity and only poor public recognition. Conservation and management efforts are caught up in a complicated nexus of interactions involving a web of commitments under international conventions and agreements, European environmental laws, and European fisheries policy. However, public disinterest, lack of political will to implement conservation measures, and complicated fishing-related issues hinder any real progress. More positively, recent advice from the International Council for the Exploration of the Seas (ICES) provides a new scientific foundation for conservation action to address fisheries bycatch in the Baltic Proper harbor porpoise population. Populations of other porpoise species (family Phocoenidae) are also threatened, most notably the global population of the critically endangered vaquita, or Gulf of California porpoise ( Phocoena sinus ). The common threats and factors affecting porpoise populations are discussed and recommendations offered.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

Editorial: People – Marine Mammal Interactions - Andy Butterworth; Mark P. Simmonds (Frontiers in Marine Science, 2017)

The International Whaling Commission—Beyond Whaling - Andrew J. Wright; Mark P. Simmonds; Barbara Galletti Vernazzani (Frontiers in Marine Science, 2016)

Does the Seal Licensing System in Scotland Have a Negative Impact on Seal Welfare? - Laetitia Nunny; Fritha Langford; Mark P. Simmonds (Frontiers in Marine Science, 2016)